"Learning to See the Person, Not the Culture or the Faith": Critical Reflections on Internationalizing Higher Education in Israel. Issue 4 (2nd October 2017) - Trahar, Sheila
Abstract : Experiences as a Work Package leader on a European Union project on internationalization of higher education in Israel motivated the author to use her research on internationalization and university teaching experiences in various countries to facilitate the Israeli partners to interrogate their pedagogical practices. Supported to engage in a pedagogy of discomfort, they confronted complexities in their higher education environment, redesigning programs to integrate principles of internationalization of the curriculum and a social justice agenda.